2021
DOI: 10.1111/anu.13329
|View full text |Cite
|
Sign up to set email alerts
|

Dietary DL‐methionyl‐DL‐methionine supplementation could improve growth performance under low fishmeal strategies by modulating TOR signalling pathway of Litopenaeus vannamei

Abstract: An 8-week feeding trial was conducted to investigate the effects of DL-methionyl-DLmethionine (Met-Met) supplementation in different fishmeal levels on growth performance, antioxidant and immune response of juvenile Pacific white shrimp, Litopenaeus vannamei. Eight isonitrogenous and isolipidic experimental diets were formulated to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Although our results indicated no significant changes of rag c even with methionine supplementation, it might be able to activate the expression of other Rag proteins. The stimulatory effect of supplementary methionine on mTOR signaling pathway has been demonstrated in previous studies ( Su et al, 2018 ; Farinha et al, 2021 ; Lu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Although our results indicated no significant changes of rag c even with methionine supplementation, it might be able to activate the expression of other Rag proteins. The stimulatory effect of supplementary methionine on mTOR signaling pathway has been demonstrated in previous studies ( Su et al, 2018 ; Farinha et al, 2021 ; Lu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 70%
“…When about 50% fishmeal was replaced, the T-CHO in plasma remained constant in the current study, and methionine supplements did not alter the T-CHO levels. Lu et al (2021) suggested that the T-CHO levels appeared to be more closely related to fishmeal levels than methionine in diets. The reduction of T-CHO content in plasma in response to methionine deficiency was observed in L. vannamei when 65% fishmeal was replaced ( Ji et al, 2021 ), while the T-CHO levels of L. vannamei exhibited no alterations when 60% fishmeal was replaced ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found, for the first time, that optimal Met-Met supplementation enhanced the capacities of T-AOC, AHR, and ASA; the activity of antioxidant enzymes including MnSOD, GPx, GST, GR, and CAT; and GSH content along with decreasing contents of ROS, MDA, and PC in juvenile grass carp intestines, suggesting that optimum Met-Met could increase antioxidant capacity in the fish gut, thereby decreasing oxidant damage. Similarly, optimal levels of Met-Met enhanced T-AOC and decreased MDA content in Nile tilapia liver [ 13 ] and in white leg shrimp plasma [ 15 ], as well as increasing hemolymph T-AOC and decreasing hepatopancreas MDA in Pacific white shrimp ( Litopenaeus vannamei ) [ 26 ]. Interestingly, the present results found that optimum Met-Met supplementation boosted the activity of MnSOD but not CuZnSOD in the intestine.…”
Section: Discussionmentioning
confidence: 99%